Biapenem Activity Against Meropenem-Resistant Klebsiella pneumoniae and Pseudomonas aeruginosa - E. M. Gordina; S. A. Bozhkova; V. V. Shabanova (Антибиотики и Химиотерапия)
Currently, the diversity of resistant strains with a certain set of resistance mechanisms is growing, and the frequency of their distribution is increasing. One of the options for finding optimal ways to treat severe infections, including orthopedic infections caused by Klebsiella pneumoniae and Pseudomonas aeruginosa, is the use of new drugs with possible activity against resistant strains.The aim of the study is comparative evaluation of biapenem antibacterial activity against meropenem-resistant K.pneumoniae and P.aeruginosa.Materials and Methods. A total of 14 K.pneumoniae and 18 P.aeruginosa isolates were included in the study. The determination of sensitivity to biapenem and meropenem was carried out via determining the minimum inhibitory concentrations (MIC) for each microorganism by the method of serial dilutions in accordance with ISO 20776-1-2010. Carbapenemases genes (MBL:VIM-, IMP- and NDM-types; OXA-48; KPC) were detected by commercially available real-time PCR.Results. The highest MIC value of meropenem was registered in the carbapenemase-producing K.pneumoniae strain (NDM and OXA-48) and amounted to 512 mg/l, while the MIC value of biapenem in this isolate was 256 mg/l. The MIC50 of meropenem was determined to be 16 mg/l, while in case of biapenem it was 4 mg/l. MIC90 of meropenem against P.aeruginosa was 512 mg/l, of biapenem — 256 mg/l. Among all meropenem-resistant strains included in this study, 28.6% K.pneumoniae and 22.2% P.aeruginosa isolates showed sensitivity to biapenem, the rest were resistant to this drug or sensitive at increased exposure.Conclusion. Comparative analysis of the antibacterial activity against meropenem-resistant K.pneumoniae and P.aeruginosa showed that MIC50/90 of biapenem is several times lower than that of meropenem. Sensitivity to this drug was recorded in 25% of the studied isolates resistant to meropenem (4 — K.pneumoniae and 4 — P.aeruginosa), which increases the possibility of using this drug in the treatment of patients with orthopedic infections.